Social Support and Residential Stability in Privately Owned Assisted Housing. (March 2019) - Beck, Kevin
Theories explaining social cohesion in assisted housing largely pivot between two positions. The first suggests that assisted renters tend to be isolated from their neighbors because they live in high–poverty neighborhoods and in housing complexes that inhibit residential interaction. The second suggests that assisted renters are not isolated but instead exchange support with their neighbors in order to mitigate material hardships. How do residents in assisted housing manage to exchange support in a context that would seem to inhibit interaction? Drawing on the American Housing Survey for data on residential mobility and the San Diego Assisted Housing Survey for data on residential interaction, I test the hypothesis that assisted housing increases residential stability, and that increased stability provides assisted renters with more opportunities to build support networks with their neighbors. I find evidence that rent subsidies slow the pace of residential mobility and those longtime residents of assisted housing are more likely to exchange support with their neighbors than residents who more recently moved in. The findings inform debates over social cohesion in assisted housing and assisted housing policy.